2003
DOI: 10.1046/j.1440-1673.2003.01172.x
|View full text |Cite
|
Sign up to set email alerts
|

Triangular cord sign and ultrasound features of the gall bladder in infants with biliary atresia

Abstract: The aim of this study was to reassess the accuracy of the triangular cord sign, the triangular cord sign coupled with abnormal gall-bladder length, and an irregular gall-bladder wall in the diagnosis of biliary atresia. The ultrasonograms of 46 infants with cholestatic jaundice were reviewed for the triangular cord sign, gall-bladder length and gall-bladder wall without knowledge of the clinical data. Of the 23 infants with biliary atresia, 22 had the triangular cord sign whereas 17 infants with other causes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 12 publications
1
11
0
2
Order By: Relevance
“…Visrutaratna et al [14] claim that the ultrasonographic triangular cord sign coupled with abnormal gallbladder length is more reliable than the ultrasonographic triangular cord sign alone or gallbladder wall irregularity in the diagnosis of biliary atresia as was found in this study where all three subjects that had a positive TC sign on USS, were confirmed at surgery and none of them had gallbladder demonstrated.…”
Section: Discussionsupporting
confidence: 53%
“…Visrutaratna et al [14] claim that the ultrasonographic triangular cord sign coupled with abnormal gallbladder length is more reliable than the ultrasonographic triangular cord sign alone or gallbladder wall irregularity in the diagnosis of biliary atresia as was found in this study where all three subjects that had a positive TC sign on USS, were confirmed at surgery and none of them had gallbladder demonstrated.…”
Section: Discussionsupporting
confidence: 53%
“…Endoscopic retrograde cholangiopancreatography (ERCP) has high sensitivity, but it requires general anesthesia in infants and depends on equipment and technical expertise that is rarely available in many pediatric centers [10,11]. The US detection of the 'triangular cord' sign has very high accuracy in experienced hands, although some authors have reported sensitivity and specificity as low as 80 and 74%, respectively [12,13]. US has also been used to determine the presence or absence of the extrahepatic bile duct with similar accuracy as the triangular cord sign [14].…”
Section: Discussionmentioning
confidence: 99%
“…Il s'agit de la polysplénie, du signe du « cône fibreux ». Le triangle hyperéchogène au hile du foie a une sensibilité, une spécificité et une valeur prédictive positive très élevées de l'ordre de 95,7 ; 73,9 ; 84,8 et 78,6 % respectivement pour le diagnostic de l'AVB [20][21][22][23][24][25][26]. Les comptes rendus des échographistes étaient incomplets pour l'AV.…”
Section: Discussionunclassified